ORGANIC FERTILIZATION AND NATURAL SUBSTANCES TREATMENTS AFFECTS CHEMICAL CONSTITUENTS OF GUAR PLANTS - SHEHATA, ABEER M.; F. A. ATTIA, R. A. TAHA, M. A. H. ABDOU, A. A. EL-SAYED, (Horticultural Biotechnology Research)
This experiment was conducted at the Floriculture Nursery, Faculty of Agriculture, Minia University during the two successive seasons to study the effect of compost at rates (0, 25, 2.50 and 3.75 ton/fed.) and natural substances i.e. vitamins (ascorbic acid at 50 and 100 ppm, ?-tocopherol at 10, 20 ppm and thiamine, at 25 and 50 ppm) and active yeast at 2.5 and 5 g/l. and their interaction on some chemical constituents of guar plants. The results indicated that, Addition of compost caused an increase in guaran %, Photosynthetic pigments, Total carbohydrates (%) N, P and K (%) and Protein (%). The maximum level in all previous traits was for the plants growing in the soil fertilized with the highest level of compost (3.75 t/fed.). Using the treatments of vit. C at 50 ppm followed by 5 g/l. active yeast, then vit. E at 10 ppm gave the highest values of all previous traits. The interaction between the two main factors (A×B) was significant for guaran %, photosynthetic pigments, total carbohydrates %, N and P %., The highest values were obtained from the interaction treatments of 3.75 ton/fed., compost in combination with active yeast at 5 g/l. and vit. C at 50 ppm. On the other hand, the interaction between compost, active yeast and vitamins treatments was not significant for protein content (%). We conclude that supply guar plants with compost at 3.75 ton/fed., and spraying plants with either active yeast at 5 g/l. or ascorbic acid (vit. C) at 50 ppm to improve the values of some chemical constituents under investigation condition.